The Combination Effect of Ceftriaxone and Chloramphenicol on Staphylococcus aureus Isolate of Diabetic Gangrene: Efek Kombinasi Seftriakson dan Kloramfenikol pada Staphylococcus aureus Isolat dari Gangren Diabetik - Purnomo, Yudi; Chandra, Pasha; Triliana, Rahma (Universitas Tadulako, 2022)
Background: Diabetic gangrene is a complication of Diabetes mellitus caused by Staphylococcus aureus. The combination of Ceftriaxone and Chloramphenicol is often used to cure gangrene infection, even though, they produce antagonist interaction based on theory. Objectives: To evaluate the potency of Ceftriaxone, Chloramphenicol and its combination on Staphylococcus aureus isolate of Diabetic gangrene. Material and Methods: The research was done by using disc diffusion methods with Muller Hinton media. Ceftriaxone, Chloramphenicol and its combination dose of 7,5 µg/ml, 15 µg/ml and 30 µg/ml, respectively were tested on Staphylococcus aureus culture taken form the diabetic gangrene patients. Antibacterial effect was observed by measuring inhibition zone on bacteria culture. Type of interaction was analyzed by Ameri-Ziaei Double Antibiotic Synergism Test (AZDAST) method. The results of study were tested statistically with One Way ANOVA (p=0.05) followed by Least Significant Difference (LSD) test. Results: The combination of Ceftriaxone and Chloramphenicol showed an antibacterial effect lower than Ceftriaxone. ß-lactam antibiotic like Ceftriaxone require the cell be growing and dividing in order to have a bactericidal action. Meanwhile, Chloramphenicol causes a slow growth of Staphylococcus aureus and impairs bactericidal effect of Ceftriaxone if they are combined. Conclusions: Ceftriaxone and Chloramphenicol combination has lower antibacterial effect than the single antibiotic groups on Staphylococcus aureus isolate of Gangrene diabetic and the type of interaction is antagonistic.